Nevirapine Increases Sodium/Iodide Symporter-Mediated Radioiodide Uptake by Activation of TSHR/cAMP/CREB/PAX8 Signaling Pathway in Dedifferentiated Thyroid Cancer - Shang, Hongxia; Zhao, Junyu; Yao, Jinming; Wang, Huanjun; Dong, Jianjun; Liao, Lin (Frontiers in Oncology, 2020)
Nevirapine has been proved to be effective in inducing re-differentiation and suppressing tumor growth in several tumor cells. This study aims to investigate the therapeutic potential of nevirapine in dedifferentiated thyroid cancer (DeTC), which refractory to radioiodine treatment and the underlying mechanisms. The results indicated that nevirapine significantly inhibited the proliferation and increased the expressions of thyroid differentiation-related genes, thyroid stimulating hormone receptor (TSHR), sodium/iodide symporter (NIS), thyroid peroxidase (TPO), and transcriptional factor paired box 8 (PAX8) in dedifferentiated thyroid cancer cells (WRO 82-1 and dFTC-133). Furthermore, nevirapine also enhanced radioiodide uptake significantly both in vitro and in vivo, and inhibited the growth of xenograft tumors. Nevirapine might improve radioiodine sensitivity via the activation of TSHR/cAMP/CREB/PAX8 signaling pathway. This study demonstrates that nevirapine could be potentially used to improve radioiodine therapeutic efficacy in dedifferentiated thyroid cancer patients.